2008
DOI: 10.1177/1534484308316486
|View full text |Cite
|
Sign up to set email alerts
|

A Response to Wang and Swanson's Article on National HRD and Theory Development

Abstract: Wang and Swanson (2008) have provided a critique of the current state of the research and theory of national human resource development (NHRD). In this article, the authors provide a critique based on the following issues: insistence on a single paradigm of truth or reality, theory development methodology, the bounding process, the definitional process, scope of NHRD efforts, and reliance on economics (and only development economics).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…The NHRD literature from HRD publications focused on priorities and policies for a number of advanced, transitioning, and emerging market economies (Lynham & Cunningham, 2006). This literature enhanced our understanding of the concept of NHRD as well as debates regarding its theoretical foundations (McLean, 2012; McLean, Lynham, Azevedo, Lawrence, & Nafukho, 2008; G. G. Wang & Swanson, 2008; J.…”
Section: Review Of Nhrd Models In the Literaturementioning
confidence: 96%
“…The NHRD literature from HRD publications focused on priorities and policies for a number of advanced, transitioning, and emerging market economies (Lynham & Cunningham, 2006). This literature enhanced our understanding of the concept of NHRD as well as debates regarding its theoretical foundations (McLean, 2012; McLean, Lynham, Azevedo, Lawrence, & Nafukho, 2008; G. G. Wang & Swanson, 2008; J.…”
Section: Review Of Nhrd Models In the Literaturementioning
confidence: 96%
“…Later, this definition was presented by McLean (2004) as a cross-national definition of HRD with a slight modification to initiate the NHRD research agenda. This involved more than 15 authors in more than 20 countres' case studies to explore NHRD phenomenon (McLean, Lynham, Azevedo, Lawrence, & Nafukho, 2008). NHRD theory is still premature, and requires further research in different country contexts based on its theory development method used so far.…”
Section: Theoretical Gap Of the Studymentioning
confidence: 99%
“…The current NHRD literature provides definitions of NHRD (McLean, 2004;Yang, D. Zang, & M. Zang, 2004;Bartlett & Rodgers, 2004;Lynham & Cunningham, 2004;Scotland, 2004;Cooper, 2004;Cox, Arkoubi, & Estrada, 2006;Hasler, Thompson, & Schuler, 2006;Cunningham, Lynham, & Weatherly, 2006); pressures and imperatives to NHRD, alternative NHRD models, importance and challenges of NHRD, attributes of excellent NHRD and its desirable outcomes (Cho & McLean, 2004;Lynham & Cunningham, 2006), theories behind NHRD (Paprock, 2006), country experiences in implementing NHRD (2004 and 2006 NHRD country's case studies), and some debates over the new emergence of NHRD (Wang, 2008;Wang, Korte, & Sun, 2008;Wang & Swanson, 2008a;McLean et al, 2008).…”
Section: Theoretical Gap Of the Studymentioning
confidence: 99%
“…philosophical and conceptual perspectives, language use, assumed boundaries and proposed locations of HRD practice (McGoldrick et al 2002a). Limiting HRD practice to the context/location of work organisations, as in Bates et al's definition, is also questioned by those who include communities and nations (McLean et al 2008) and higher education institutions (Doloriert et al 2012) as locations of HRD practice. This definition has some resonance with an earlier definition from the USA by Bates et al, who suggested the purpose of HRD is to enhance learning, human potential and high performance in work-related systems.…”
Section: Evaluating the Evaluation Frameworkmentioning
confidence: 99%